The savvy investor's guide to building wealth through traditional investments - Baker, H. Kent 1944-; Nofsinger, John R.; Spieler, Andrew C. (Savvy investor's guide, 2020)
Would you like to be a millionaire? If you're like most people, your answer is "yes". But unlike popular opinion, this goal is not beyond your reach. Building wealth is more common sense than secret formula. You need to invest wisely. This easy-to-read guide focuses on traditional investments - stocks, bonds, and cash or cash equivalents. Stocks and bonds are the heartbeat of Wall Street. Finance experts H. Kent Baker, John R. Nofsinger, and Andrew C. Spieler take you through how to invest in a single security, as well as mutual funds and exchange-traded funds (ETFs), which offer many potential benefits to individual investors. This practical and straightforward book is written for novice investors. It takes an innovative question-and-answer format to help you learn about traditional investments and to become a better investor. If you want to become a millionaire, and don't have the luck of buying a winning lottery ticket, this guide is for you.